Bone remodeling serum markers in children with systemic lupus erythematosus - Sheng Hao; Jing Zhang; Bingxue Huang; Dan Feng; Xiaoling Niu; Wenyan Huang (BMC, 2022)
Abstract Indroduction SLE is an autoimmune multisystem disease. Glucocorticoid is an irreplaceable medication for SLE. Glucocorticoid and inflammatory mediators impact bone remodeling by OPG/RANKL/RANK signal system, which could lead to osteoporosis. Our aim is to detect the expression of RANKL/OPG in children with SLE, and to preliminarily explore the changes of bone remodeling serum markers in children with SLE. Methods Serum RANKL and OPG of 40 children with SLE and healthy children were detected by ELISA, while 25(OH)VitD3 was detected routinely. Clinical data of children with SLE were recorded, including gender, age, height, weight, BMI, SLEDAI, duration of the disease, cumulative dose of glucocorticoid, and correlation analysis was conducted with RANKL, OPG and 25(OH)VitD3. Results Serum RANKL concentrations in SLE group were significantly higher than health group (9.82 ± 7.20 vs. 6.80 ± 4.35 pg/ml and 0.081 ± 0.072 vs. 0.042 ± 0.034, P < 0.05) respectively, and the concentrations of OPG and 25(OH)VitD3 in serum were significantly lower than health group (156.34 ± 57.33 vs. 189.16 ± 68.70 pg/ml and 43.66 ± 31.27 vs. 59.04 ± 21.56 mmol/L, P < 0.05). Serum RANKL in children with SLE was positively correlated with the duration of SLE, cumulative dose of GC(r = 0.593, 0.727, P < 0.05). And it was negatively correlated with serum OPG and 25(OH)VitD3 (r = -0.601, -0.469, P < 0.05). In addition, serum OPG and 25(OH)VitD3 concentrations were inversely correlated with cumulative dose of GC (r = -0.66, -0.508, P < 0.05). Conclusion Low levels of vitamin D3 and bone metabolic abnormalities still persist in children with SLE even if the disease is in remission, while serum RANKL level was elevated, OPG expression was reduced. In the case of disease remission, GC is involved in the occurrence and development of abnormal bone remodeling through RANKL/OPG.